Different murine-derived feeder cells alter the definitive endoderm differentiation of human induced pluripotent stem cells - Shoji, Masaki (PLoS One, 2018)
The crosstalk between cells is important for differentiation of cells. Murine-derived feeder cells, SNL76/7 feeder cells (SNLs) or mouse primary embryonic fibroblast feeder cells (MEFs) are widely used for culturing undifferentiated human induced pluripotent stem cells (hiPSCs). It is still unclear whether different culture conditions affect the induction efficiency of definitive endoderm (DE) differentiation from hiPSCs. Here we show that the efficiency of DE differentiation from hiPSCs cultured on MEFs was higher than that of hiPSCs cultured on SNLs. The qPCR, immunofluorescent and flow cytometry analyses revealed that the expression levels of mRNA and/or proteins of the DE marker genes, SOX17, FOXA2 and CXCR4, in DE cells differentiated from hiPSCs cultured on MEFs were significantly higher than those cultured on SNLs. Comprehensive RNA sequencing and molecular network analyses showed the alteration of the gene expression and the signal transduction of hiPSCs cultured on SNLs and MEFs. Interestingly, the expression of non-coding hXIST exon 4 was up-regulated in hiPSCs cultured on MEFs, in comparison to that in hiPSCs cultured on SNLs. By qPCR analysis, the mRNA expression of undifferentiated stem cell markers KLF4, KLF5, OCT3/4, SOX2, NANOG, UTF1, and GRB7 were lower, while that of hXIST exon 4, LEFTY1, and LEFTY2 was higher in hiPSCs cultured on MEFs than in those cultured on SNLs. Taken together, our finding indicated that differences in murine-feeder cells used for maintenance of the undifferentiated state alter the expression of pluripotency-related genes in hiPSCs by the signaling pathways and affect DE differentiation from hiPSCs, suggesting that the feeder cells can potentiate hiPSCs for DE differentiation.